Development of an image rotary encoder for motion control - Ismayuzri, Ishak (2013)
A rotary encoder reads rotational motion (angular position and speed) and converts the motion into electrical signals. It involves two components: a designed coded-disc to represents rotational information and a sensor to convert the coded information into electrical signals. A conventional rotary encoder uses three major elements, a pattern code disc, a light source and a photo-detector. Factors affecting rotary encoder are mechanical component alignments, resolution enhancement, size reduction, additional processing electronics and the working environment. Depending on the design of the coded-disc and the signal interpolation, a rotary encoder can function as an absolute or incremental encoder. An absolute encoder can determine the angular position without the need to have a reference position. On the other hand, an incremental encoder requires a reference position in order to determine the angular position. In operations, when an incremental encoder is started, the system has to move to the home position in order to set a reference point. An absolute encoder does not require home operations because it knows exactly the current angular position. As such, an incremental encoder requires an additional power supply when the system is turn-off so that it can “memorize” the current position. An absolute encoder is more expensive and the angular position range is limited by the disc size. Many researchers proposed and implemented different alternatives to absolute encoder. One technique is using an image rotary encoder. Current trends in digital image processing techniques have been applied widely into various applications. Some of the applications emerge as a sensing device with the assist of digital image processing techniques. Therefore, the research objective is to develop an image rotary encoder based on image texture before converting it into speed and motion data. The image texture is captured from a specially-designed texture of rotating disc using a digital image sensor. The proposed image rotary encoder is based on pixel changes by motion of rotating disc. The captured images are then converted into motion data by an image processing algorithm. The output signal is a binary position code which is similar to the conventional absolute rotary encoder. Performance of the image rotary encoder is validated by comparing the speed and position with the conventional rotary encoder. Experimental results indicate that the speed and position measured by the developed image rotary encoder are directly proportional to those measured using the conventional rotary encoder. Experiments also confirmed that the developed image rotary encoder can be utilized as a feedback device to a DC motor PID position control. Therefore, the developed image rotary encoder successfully functions as an absolute rotary encoder.